Propriedade intelectual como instrumento do etnodesenvolvimento: oportunidades na Região Imediata Soure-Salvaterra, Marajó, Pará - RODRIGUES, Kildren Pantoja (Universidade Federal do Pará, 2023)
The theory of ethnodevelopment can be used as a governance guideline for the territorial management of spaces where there are traditional peoples and/or communities, with the main aim of treating the culture of these populations as a fundamental input for their development, respecting, protecting and maintaining the managerial autonomy of such communities. It is defended that traditional knowledge must be used for the benefit of the people who hold it, and that should occurs through direction and advice by the State. For this guideline to be used efficiently, it is necessary to carry out a plan, strategically listing how such management can be carried out. In this perspective, this study presents the management of the Intellectual Property of these peoples as an effective instrument for the application of the main pillar of ethnodevelopment, that is the observance and use of traditional culture fundamentally for the benefit of the local development of the territory where such peoples and traditional communities inhabit. It is demonstrated how such direction presents itself as a true historical reparation with regard to the history of Brazil in relation to the treatment of the original cultures and those coming from the African continent, as well as listing, in detail, the legal content that underlies the use of ethnodevelopment in territories where traditional peoples and communities are found. It also explains how the Intellectual Property tools present in Brazilian legislation can be used for this purpose. From this perspective, the field research carried out in two communities of the Marajó archipelago, located in the immediate Soure-Salvaterra region, is approached, demonstrating, based on verified facts, how this Intellectual Property management can be beneficial for the Marajoara region, and, consequently, to the Amazon region. Finally, the results of this research are presented, demonstrating which are the potential products based on traditional Marajoara knowledge that have marketing strength from the application of Intellectual Property management. It is concluded that there is a latent need for public policies that use Intellectual Property legislation in favor of the local development of traditional peoples and communities, as demonstrated in the Marajoara localities in the present research studied, strengthening this statement based on the entire national legal framework relating to the matter. Finally, a little atlas of the studied region is presented with all the cartography elaborated especially for this academic work.